2017
DOI: 10.1136/bmjopen-2017-018476
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies and ethnic distribution of ABO and RhD blood groups in China: a population-based cross-sectional study

Abstract: ObjectivesABO and RhD blood groups are key factors affecting blood transfusion safety. The distribution of ABO and RhD blood groups varies globally, but limited data exist for ethnic distributions of these blood groups in Asian populations. We aimed to evaluate the distribution of ABO and RhD blood groups among Chinese ethnic groups.DesignA population-based cross-sectional study.SettingData on ABO groups and ethnicities were obtained from the National Free Preconception Health Examination Project (NFPHEP) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 20 publications
2
55
4
1
Order By: Relevance
“…Similar studies conducted elsewhere agree with the high proportion of O+ and the low incidence of AB− observed in our study. For example, the formulas O+ > A+ > B+ > AB+ > O− > B− > A− > AB− (Shrestha et al, ), O+ > A+ > B+ > AB+ > A− > O− = B− > AB− (Liu et al, ), O+ > A+ > B+ > AB+ > O− > A− > B− > AB− (Ndoula et al, ) and O+ > A+ > B+ > O− > A− > B− > AB+ > AB− (Golassa et al, ) have been reported for a Nepalese, Chinese, Cameroonian and an Ethiopian population, respectively. Contrary to this, two studies in India reported a predominance of B+ in their populations: B+ > O+ > A+ > AB+ > B− > A− > O− > AB− (Garg et al, ) and B+ > O+ > A+ > AB+ > B− > O− > A− > AB− (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies conducted elsewhere agree with the high proportion of O+ and the low incidence of AB− observed in our study. For example, the formulas O+ > A+ > B+ > AB+ > O− > B− > A− > AB− (Shrestha et al, ), O+ > A+ > B+ > AB+ > A− > O− = B− > AB− (Liu et al, ), O+ > A+ > B+ > AB+ > O− > A− > B− > AB− (Ndoula et al, ) and O+ > A+ > B+ > O− > A− > B− > AB+ > AB− (Golassa et al, ) have been reported for a Nepalese, Chinese, Cameroonian and an Ethiopian population, respectively. Contrary to this, two studies in India reported a predominance of B+ in their populations: B+ > O+ > A+ > AB+ > B− > A− > O− > AB− (Garg et al, ) and B+ > O+ > A+ > AB+ > B− > O− > A− > AB− (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of blood group systems is of key importance in clinical practice. The frequency distribution in any population is useful for effective management of blood bank inventory and for safe transfusion services, especially during emergency situations (Liu et al, ). The ABO and Rh blood groups are also useful in clinical studies, population genetic studies, researching into population migration patterns as well as resolving certain medico‐legal issues, particularly of disputed paternity cases (Garg, Upadhyay, Chufal, Hasan, & Tayal, ).…”
Section: Introductionmentioning
confidence: 99%
“…ABO and RhD blood groups, the most well-known blood group systems, are of key importance for transfusion safety and clinical practice and are also thought to be linked with disease susceptibility [4]. The distribution of ABO and RhD blood groups varies globally [5]. Ethnicities differ in prevalence of blood groups and antigens.…”
Section: Introductionmentioning
confidence: 99%
“…This is a particular concern for Stanford Health Care (SHC) and Stanford Blood Center (SBC) because of the demographics of our region. The California Bay Area has a relatively larger percentage of Asian residents compared to the United States, and various studies have shown these populations to have a much lower frequency of O‐negative blood type …”
mentioning
confidence: 99%
“…The California Bay Area has a relatively larger percentage of Asian residents compared to the United States, and various studies have shown these populations to have a much lower frequency of O-negative blood type. 5,[9][10][11] In this paper, we approached the problem of inappropriate ON-RBC utilization in a data-driven manner. First, we identified that indeed our ON-RBC donors comprise a much smaller proportion of our overall donor base.…”
mentioning
confidence: 99%